Geopark sebagai peraga pembangunan lestari wilayah - Ibrahim Komoo (Universiti Kebangsaan Malaysia, 2010)
Geopark is an innovative conservation approach for protection of the heritage, and encourage scientific research, public education and local economic development. Initially, a geopark is defined as a nationally protected area containing a number of geological heritage sites of particular importance, rarity or aesthetic appeal, which can be developed as part of an integrated concept of protection, education and sustainable development. Recently, the concept of geopark has evolved and not just restricted to protected areas. It has become a development tool or branding of an area, taking into consideration the balance between nature-culture conservation, geotourism activities and local community well-being. Within the conservation program, the emphasis is not only to protect geoheritage sites, but it encourages the biodiversity and cultural heritage to be conserved in an integrated manner. The introduction of geotourism as a special tourism product has also triggered the popularisation of knowledge-based tourism, which promotes higher income economy with lower impacts to natural resources. Local community is becoming more engaged and actively participating in the development of geopark, thus able to take the opportunity to enhance their economic activities. This article highlights the history and the evolution of geopark concept towards promoting regional sustainable development. The model is introduced based on a development framework that gives emphasis to three important components: heritage conservation; community development; and economic development. In line with this framework, the evolution of Langkawi as a member of the Global Geoparks Network focuses on conservation of heritage resource development, environmentally friendly tourism infrastructure development and the availability of innovative heritage resource-based tourism products.